Figurative Language in Students’ English Book - Sri Minda (Asian TESOL Journal, 2021)
This research was carried out to investigate the types of figurative language found in reading texts at grade X students’ book, the dominant type of figurative language and to find out the students’ difficulties in understanding the figurative language. The design of the research was qualitative in which content analysis research was conducted. The source of the data was high school students’ English textbook in Padangsidimpuan. The instrument to collect the data was content analysis checklist, test and interview. Some of the students were interviewed by the researcher to know their responses on the use of figurative language. The data was analyzed based on three theories proposed by Keraf. The findings of this research are: there are 6 types of figurative language in English reading text at grade X students’ book. They are personification, hyperbole, metonymy, euphemism, antithesis, and repetition, the dominant types found in this text are personification; and the students’ difficulties in understanding the language are lacking of the linguistic knowledge that is semantic meaning and lacking of socio-cultural understanding in the phrases and sentences.